รูปแบบการจัดการการท่องเที่ยวเชิงสุขภาพ กรณีศึกษา : อำเภอปากช่อง จังหวัดนครราชสีมา - ทรงสายชลชัย, นพรัตน์; เจริญศิลป์, วัลย์ลิกา; สักพันธ์, ปรเมษฐ์; พรหมภู่, พุธิตา (ช่อดอกปีบปริทัศน์, 2025)
Research on The Health tourism management model, study: Pak Chong District, Nakhon Ratchasima Province The objective is to study the potential of managing health tourism. Case study: Pak Chong District, Nakhon Ratchasima Province. To study the model for managing health tourism. Case study: Pak Chong District, Nakhon Ratchasima Province. To study problems, obstacles, and solutions in health tourism management. Case study: Pak Chong District, Nakhon Ratchasima Province It is qualitative research. The research instrument used was an in-depth interview. The research team analyzed the data descriptively. Content analysis and essential analysis. From research it was found that Potential for managing health tourism in Pak Chong District, Nakhon Ratchasima Province There are forests and abundant nature and fresh air. It has the seventh best source of ozone in the world. There are many amenities such as food, accommodation, and health tourism management models. Pak Chong District has a variety of formats to choose from according to your needs, such as traditional Thai medicine, rural herbs, healthy food. natural agriculture and natural resources the aim is to preserve one's health. There is a problem of garbage disposal in tourist attractions, roads, and obstacles in traveling that must be encountered with traffic jams. The entry of wild animals creates distress. Guidelines for solving the problem are as follows: Motorists should create good conscience in using the road. and study shortcut routes or other routes and create signs to dispose of garbage correctly and increase the number of trash cans to meet the number of tourists.